Analisis Kemampuan Berpikir Kreatif Siswa Smp Kelas Viii Pada Materi Sistem Persamaan Linear Dua Variabel Ditinjau Dari Gaya Kognitif - Kartikasari, Kartikasari; Muhtarom, Muhtarom; Sudargo, Sudargo (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2023)
This research was conducted with the aim of describing the creative thinking abilities of Grade VIII junior high school students with the characteristics of fieldindependent cognitive style students in solving math problems on SPLDV material. Theapproach used in this study is a qualitative approach. The subject of this study was classVIII F students of SMP Negeri 36 Semarang for the academic year 2022/2023, with a totalof 1 person, namely students with the FI cognitive style. Subjects were determined bycarrying out the GEFT test to determine students' cognitive styles. The data collectionmethod used in this study used written data from the SPLDV test and interviews. TheSPLDV test is adjusted to indicators of creative thinking, namely fluency, flexibility andnovelty. The data analysis technique used is data reduction, data presentation and conclusion. Data validity checking techniques using source triangulation. The results of this study indicate that students with the FI cognitive style fulfill all indicators of creativethinking, namely fluency, flexibility and novelty.